Downside of family motivation; impact of family motivation on job burnout through emotional labor - Hameed, Kamran; Ghaffar, Abdul; Arshed, Noman (The journal of contemporary issues in business and government, 2021)
Extending the efforts of earlier studies, this study investigated the relationship between family motivation and job burnout.Viamediating mechanism of emotional labor by using conservation of resource (COR) theory as a framework. Itcontributes to the existing literature by exploring relatively new phenomenaof family motivation.Whereby the employees’ family motivation distracts them from performingtheir duties, exerting more emotional labor, which increases job burnout. The relevancy of family motivation is increased under the work from home situation because of COIVID19. A total of 189 full-time employees, working in both public and private sector organizations in Pakistan, were observed. The findings revealed that family motivation is positively related tojob burnout, and this relationship is mediated by emotional labor at the workplace. The findings of the study are discussed in terms of their theoretical and practical implications.